A high entropy ceramic material and its preparation method and application
By using high-entropy ceramic materials (Hf(1-x)/4Zr(1-x)/4Ce(1-x)/4Pr(1-x)/4Yx)O2-δ, the existing thermal barrier coating materials exhibit insufficient resistance in CMAS corrosion is solved, and the efficient resistance to CMAS corrosion is achieved, and the stability and temperature bearing capacity of the coating are significantly improved.
Patent Information
- Application Number
- CN202411900625.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Existing thermal barrier coating materials show insufficient resistance when facing CMAS corrosion, resulting in premature coating failure and insufficient temperature bearing capacity.
High-entropy ceramic material (Hf(1-x)/4Zr(1-x)/4Ce(1-x)/4Pr(1-x)/4Yx)O2-δ is prepared by specific preparation methods, including pretreatment, ball milling, drying, grinding, sieving, pressing and firing of oxide powder, and other steps.
When facing CMAS corrosion, this high-entropy ceramic material effectively prevents CMAS from further penetrate into the ceramic layer by forming a corrosion reaction layer of long strip apatite and block cubic phases, reducing the corrosion depth, and significantly improving the anti-CMAS corrosion performance of the thermal barrier coating.
Smart Images

Figure CN119350026B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermal barrier coating technology, specifically relating to a high-entropy ceramic material, its preparation method, and its application. Background Technology
[0002] Thermal barrier coatings (TBCs) are a key technology for improving the temperature resistance of aero-engines. However, with the continuous increase in the operating temperature of aero-engines, molten environment deposit (CMAS) corrosion has gradually become the main form of TBC failure. Traditional TBC materials, such as yttria-stabilized zirconia (YSZ), suffer from premature failure and insufficient temperature resistance, and can no longer meet the requirements of aero-engines to resist high-temperature oxidation, thermal shock, and external corrosion. Therefore, there is an urgent need to develop new TBC materials with excellent comprehensive properties such as low thermal conductivity, high hardness, and high-temperature corrosion resistance. Rare earth fluorite oxides have characteristics such as low thermal conductivity, high hardness, excellent phase stability, and high-temperature corrosion resistance, showing great potential in the field of TBC materials. They can be used to develop more superior and reliable TBC materials, providing strong support for the development of aero-engines. Summary of the Invention
[0003] In view of the above-mentioned prior art, the present invention discloses a high-entropy ceramic material, its preparation method and application, so as to solve the technical problem of weak resistance to CMAS corrosion of thermal barrier coating materials in the prior art.
[0004] To achieve the above objectives, the technical solution adopted by the present invention is: to provide a high-entropy ceramic material with the chemical formula (Hf (1-x) / 4 Zr (1-x) / 4 Ce (1-x) / 4 Pr (1-x) / 4 Y x )O 2-δ , where the value of X ranges from 0.08 to 0.4, and the value of δ ranges from 0.1 to 0.4.
[0005] This invention also discloses a method for preparing this high-entropy ceramic material, which includes the following steps:
[0006] S1: The pretreated oxide powders are mixed according to their elemental composition in the chemical formula, and then the mixture is mixed with a dispersant and ball-milled to obtain slurry A. The oxide powders include ZrO2 powder, HfO2 powder, CeO2 powder, and Pr6O. 11 Powder and Y2O3 powder;
[0007] S2: The slurry A is dried, ground, sieved and pressed to obtain a preform;
[0008] S3: Firing the preform, then crushing the fired preform into powder, mixing the powder with the dispersant and ball milling to obtain slurry B;
[0009] S4: Dry, grind, sieve, granulate and press slurry B to obtain an embryo;
[0010] S5: Firing the embryo results in the final product.
[0011] Based on the above technical solution, the present invention can be further improved as follows.
[0012] Furthermore, the pretreatment of the oxide powder in step S1 is as follows: calcination at 800~1000℃ for 2~3 hours; the particle size of the oxide powder is 40~100nm; ZrO2 powder, HfO2 powder, CeO2 powder, Pr6O 11 The purity of the powder and Y2O3 powder is ≥99.9%.
[0013] Furthermore, the dispersant is anhydrous ethanol, and the mass ratio of oxide powder to anhydrous ethanol in step S1 is 1:0.5~0.6.
[0014] Furthermore, in step S1, the ball milling speed is 300~400 rpm and the ball milling time is 12~48 h.
[0015] Furthermore, in step S2, the drying temperature is 70~90℃, the drying time is 12~24h, the grinding time is 5~7min, the sieve mesh size is 300~500 mesh, and the tablet is pressed using a tablet press with a pressure of 10~20MPa and a pressing time of 8~10min.
[0016] Furthermore, in step S3, the firing temperature is 1200~1400℃, the firing time is 25~50min; the mass ratio of powder to anhydrous ethanol is 1:0.5~0.6; the ball milling speed is 400~500rpm, and the ball milling time is 20~50h.
[0017] Furthermore, in step S4, the drying temperature is 80~100℃, the drying time is 20~40h, the grinding time is 5~7min, the sieve mesh size is 500~600 mesh, and the granulation operation is as follows: add 8% polyvinyl alcohol by weight to the sieved mixed powder and grind for 5~7min.
[0018] Furthermore, the compression operation in step S4 is as follows: use a tablet press to maintain pressure at 20~40MPa for 10~20min, and then maintain pressure at 250~300MPa for 5~8min.
[0019] Furthermore, the firing method in step S5 is as follows: the temperature is raised to 1000℃ at a heating rate of 10℃ / min, then raised to 1550℃ at a heating rate of 5℃ / min, held at that temperature for 20 hours, then raised to 1800℃ at a heating rate of 5℃ / min, and then the heating is stopped and cooled to room temperature.
[0020] This invention also discloses the application of this high-entropy ceramic material in the preparation of thermal barrier coating materials.
[0021] The beneficial effects of this invention are: the high-entropy ceramic material in this invention is a novel rare-earth fluorite oxide-based ceramic material, with the chemical formula (Hf... (1-x) / 4 Zr (1-x) / 4 Ce (1-x) / 4 Pr (1-x) / 4 Y x )O 2-δ The value of X ranges from 0.08 to 0.4, and the value of δ ranges from 0.1 to 0.4. It has excellent resistance to CMAS corrosion. When high-entropy ceramic materials come into contact with molten environment deposits, the rare earth elements contained in the material react with Ca and Si that have penetrated into the molten environment deposits to form elongated apatite (Ca2RE8(SiO4)6O2). The elongated apatite and the massive cubic phase (c-ZrO2) constitute the corrosion reaction layer. The corrosion reaction layer prevents the molten environment deposits from further penetrating into the ceramic layer and reduces the corrosion depth. It can be applied to the preparation of thermal barrier coating materials. Attached Figure Description
[0022] Figure 1 XRD diffraction patterns of the examples and comparative samples;
[0023] Figure 2 This is a scanning electron microscope image of the sample from Example 1;
[0024] Figure 3 This is a scanning electron microscope image of the sample from Example 2;
[0025] Figure 4 This is a scanning electron microscope image of the sample from Example 3;
[0026] Figure 5 The image shows a scanning electron microscope (SEM) image of sample 1 (Comparative Example 1).
[0027] Figure 6 Elemental distribution diagrams for the examples and comparative samples;
[0028] Figure 7 The images show cross-sectional scanning electron microscope (SEM) images of the samples from the examples and comparative examples after 1 hour of CMAS etching.
[0029] Figure 8 The images show cross-sectional scanning electron microscope (SEM) images of the example and comparative samples after CMAS etching for 4 hours.
[0030] Figure 9 The images show cross-sectional electron microscope (SEM) scans of the example and comparative samples after CMAS etching for 12 hours. Detailed Implementation
[0031] The specific embodiments of the present invention will be described in detail below with reference to examples.
[0032] Example 1
[0033] A high-entropy ceramic material with the chemical formula (Hf) 0.23 Zr 0.23 Ce 0.23 Pr 0.23 Y 0.08 )O 1.8 Its preparation method includes the following steps:
[0034] S1: ZrO2 powder, HfO2 powder, CeO2 powder, and Pr6O powder with a particle size of 40~100nm are mixed. 11 The powders ZrO2, HfO2, CeO2, and Pr6O3 were placed in zirconium oxide crucibles and calcined at 900℃ for 2.5 h to remove moisture and organic impurities, ensuring that the purity of each oxide powder was ≥99.9%. Then, according to the molar ratio of Hf, Zr, Ce, Pr, and Y of 0.23:0.23:0.23:0.23:0.08, the calcined ZrO2 powder, HfO2 powder, CeO2 powder, and Pr6O3 powder were added... 11 The powder and Y2O3 powder were placed in a zirconia ball mill jar, and anhydrous ethanol and zirconia balls were added for ball milling. The mass ratio of zirconia balls, oxide powder and anhydrous ethanol was 2:1:0.6. The ball milling speed was 350 rpm, and after ball milling for 24 hours, a uniformly mixed slurry A was obtained.
[0035] S2: Place slurry A in a drying oven and dry it at 80°C for 18 hours to obtain a dry mixed powder. Then grind the dry mixed powder with a mortar and pestle for 6 minutes. Then sieve the ground mixed powder through a 400-mesh sieve. Then introduce the sieved mixed powder into a cylindrical briquetting mold and press it with a tablet press at a pressure of 15 MPa for 10 minutes to obtain a preform.
[0036] S3: Place the preform into an alumina crucible and fire it in a sintering furnace at a temperature of 1300℃ for 30 minutes. Then, crush the fired preform into powder and add anhydrous ethanol and zirconium oxide microspheres to the powder. The mass ratio of zirconium oxide microspheres, oxide powder and anhydrous ethanol is 2:1:0.6. The ball milling speed is 450 rpm and the ball milling is carried out for 36 hours to obtain a uniformly mixed slurry B.
[0037] S4: Place slurry B in a drying oven and dry it at 90℃ for 30 hours to obtain a dry mixed powder. Then grind it with a mortar and pestle for 6 minutes. After grinding, sieve the ground mixed powder through a 500-mesh sieve. Add 8% polyvinyl alcohol by weight to the sieved mixed powder and grind for 6 minutes to granulate. Then, put the obtained granules into a cylindrical briquetting mold and press them with a tablet press. First, press the tablets at a pressure of 30MPa for 15 minutes to obtain a preform. Then, press the tablets at a pressure of 300MPa for 7 minutes to obtain the preform.
[0038] S5: The preform is placed in an alumina crucible and fired in a sintering furnace. The furnace is heated from room temperature to 1000℃ at a rate of 10℃ / min, then to 1550℃ at a rate of 5℃ / min, and held at that temperature for 20 hours. Finally, the temperature is increased to 1800℃ at a rate of 5℃ / min, then the heating is stopped, and the preform is cooled to room temperature to obtain (Hf). 0.23 Zr 0.23 Ce 0.23 Pr 0.23 Y 0.08 )O 1.8 .
[0039] Example 2
[0040] A high-entropy ceramic material with the chemical formula (Hf) 0.2 Zr 0.2 Ce 0.2 Pr 0.2 Y 0.2 )O 1.9 Its preparation method includes the following steps:
[0041] S1: ZrO2 powder, HfO2 powder, CeO2 powder, and Pr6O powder with a particle size of 40~100nm are mixed. 11 The powders ZrO2, HfO2, CeO2, and Pr6O3 were placed separately in zirconium oxide crucibles and calcined at 800℃ for 3 hours to remove moisture and organic impurities, ensuring that the purity of each oxide powder was ≥99.9%. Then, according to the molar ratio of Hf, Zr, Ce, Pr, and Y of 0.2:0.2:0.2:0.2:0.2, the calcined ZrO2 powder, HfO2 powder, CeO2 powder, and Pr6O3 powder were added. 11 The powder and Y2O3 powder were placed in a zirconia ball mill jar, and anhydrous ethanol and zirconia balls were added for ball milling. The mass ratio of zirconia balls, oxide powder and anhydrous ethanol was 2:1:0.5. The ball milling speed was 300 rpm, and after ball milling for 12 hours, a uniformly mixed slurry A was obtained.
[0042] S2: Place slurry A in a drying oven and dry it at 70℃ for 12 hours to obtain a dry mixed powder. Then grind the dry mixed powder with a mortar and pestle for 5 minutes. Then sieve the ground mixed powder through a 300-mesh sieve. Then introduce the sieved mixed powder into a cylindrical briquetting mold and press it with a tablet press at a pressure of 10MPa for 8 minutes to obtain a preform.
[0043] S3: Place the preform into an alumina crucible and fire it in a sintering furnace at a temperature of 1200℃ for 50 minutes. Then, crush the fired preform into powder and add anhydrous ethanol and zirconium oxide microspheres to the powder. The mass ratio of zirconium oxide microspheres, oxide powder and anhydrous ethanol is 2:1:0.6. The ball milling speed is 400 rpm and the ball milling is 50 hours to obtain a uniformly mixed slurry B.
[0044] S4: Place slurry B in a drying oven and dry it at 80℃ for 40 hours to obtain a dry mixed powder. Then grind it with a mortar and pestle for 7 minutes. After grinding, sieve the ground mixed powder through a 500-mesh sieve. Add 8% polyvinyl alcohol by weight to the sieved mixed powder and grind for 5 minutes. Then, put the ground particles into a cylindrical briquetting mold and press them with a tablet press. First, press the tablet for 10 minutes under a pressure of 20MPa to obtain a preform. Then, press the tablet for 5 minutes under a pressure of 250MPa to obtain the preform.
[0045] S5: The preform is placed in an alumina crucible and fired in a sintering furnace. The furnace is heated from room temperature to 1000℃ at a rate of 10℃ / min, then to 1550℃ at a rate of 5℃ / min, and held at that temperature for 20 hours. Finally, the temperature is increased to 1800℃ at a rate of 5℃ / min, then the heating is stopped, and the preform is cooled to room temperature to obtain (Hf). 0.2 Zr 0.2 Ce 0.2 Pr 0.2 Y 0.2 )O 1.9 .
[0046] Example 3
[0047] A high-entropy ceramic material with the chemical formula (Hf) 0.15 Zr 0.15 Ce 0.15 Pr 0.15 Y 0.4 )O 1.6 Its preparation method includes the following steps:
[0048] S1: ZrO2 powder, HfO2 powder, CeO2 powder, and Pr6O powder with a particle size of 40~100nm are mixed. 11 The powders ZrO2, HfO2, CeO2, and Pr6O3 were placed separately in zirconium oxide crucibles and calcined at 1000℃ for 2 hours to remove moisture and organic impurities, ensuring that the purity of each oxide powder was ≥99.9%. Then, according to the molar ratio of Hf, Zr, Ce, Pr, and Y of 0.15:0.15:0.15:0.15:0.4, the calcined ZrO2 powder, HfO2 powder, CeO2 powder, and Pr6O3 powder were added. 11 The powder and Y2O3 powder were placed in a zirconia ball mill jar, and anhydrous ethanol and zirconia balls were added for ball milling. The mass ratio of zirconia balls, oxide powder and anhydrous ethanol was 2:1:0.6. The ball milling speed was 400 rpm, and after ball milling for 48 hours, a uniformly mixed slurry A was obtained.
[0049] S2: Place slurry A in a drying oven and dry it at 90℃ for 24 hours to obtain a dry mixed powder. Then grind the dry mixed powder with a mortar and pestle for 7 minutes. Then sieve the ground mixed powder through a 500-mesh sieve. Then introduce the sieved mixed powder into a cylindrical briquetting mold and press it with a tablet press at a pressure of 20MPa for 10 minutes to obtain a preform.
[0050] S3: Place the preform into an alumina crucible and fire it in a sintering furnace at a temperature of 1400℃ for 25 minutes. Then, crush the fired preform into powder and add anhydrous ethanol and zirconium oxide microspheres to the powder. The mass ratio of zirconium oxide microspheres, oxide powder and anhydrous ethanol is 2:1:0.5. The ball milling speed is 500 rpm and the ball milling is 20 hours to obtain a uniformly mixed slurry B.
[0051] S4: Place slurry B in a drying oven and dry it at 100℃ for 20 hours to obtain a dry mixed powder. Then grind it in a mortar for 5 minutes. After grinding, sieve the ground mixed powder through a 600-mesh sieve. Add 8% polyvinyl alcohol by weight to the sieved mixed powder and grind for 7 minutes to granulate. Then, put the obtained granules into a cylindrical briquetting mold and press them using a tablet press. First, press the tablets at a pressure of 40MPa for 20 minutes to obtain a preform. Then, press the tablets at a pressure of 300MPa for 8 minutes to obtain the preform.
[0052] S5: The preform is placed in an alumina crucible and fired in a sintering furnace. The furnace is heated from room temperature to 1000℃ at a rate of 10℃ / min, then to 1550℃ at a rate of 5℃ / min, and held at that temperature for 20 hours. Finally, the temperature is increased to 1800℃ at a rate of 5℃ / min, then the heating is stopped, and the preform is cooled to room temperature to obtain (Hf). 0.15 Zr 0.15 Ce 0.15 Pr 0.15 Y 0.4 )O 1.6 .
[0053] Comparative Example 1
[0054] A ceramic material with the chemical formula (ZrO2). 0.92 (Y2O3) 0.08 Its preparation method includes the following steps:
[0055] S1: ZrO2 powder and Y2O3 powder were placed in zirconium oxide crucibles and calcined at 900℃ for 2.5h to remove moisture and organic impurities from the oxide powders. Then, according to the mass ratio of ZrO2 to Y2O3 of 92:8, the calcined ZrO2 powder and Y2O3 powder were placed in a zirconium oxide ball mill jar, and anhydrous ethanol and zirconium oxide balls were added for ball milling. The mass ratio of zirconium oxide balls, oxide powder and anhydrous ethanol was 2:1:0.6. The ball milling speed was 350rpm, and after ball milling for 24h, a uniformly mixed slurry A was obtained.
[0056] S2: Place slurry A in a drying oven and dry it at 80°C for 18 hours to obtain a dry mixed powder. Then grind the dry mixed powder with a mortar and pestle for 6 minutes. Then sieve the ground mixed powder through a 400-mesh sieve. Then introduce the sieved mixed powder into a cylindrical briquetting mold and press it with a tablet press at a pressure of 15 MPa for 10 minutes to obtain a preform.
[0057] S3: Place the preform into an alumina crucible and fire it in a sintering furnace at a temperature of 1300℃ for 30 minutes. Then, crush the fired preform into powder and add anhydrous ethanol and zirconium oxide microspheres to the powder. The mass ratio of zirconium oxide microspheres, oxide powder and anhydrous ethanol is 2:1:0.6. The ball milling speed is 450 rpm and the ball milling is carried out for 36 hours to obtain a uniformly mixed slurry B.
[0058] S4: Place slurry B in a drying oven and dry it at 90℃ for 30 hours to obtain a dry mixed powder. Then grind it with a mortar and pestle for 6 minutes. After grinding, sieve the ground mixed powder through a 500-mesh sieve. Add 8% polyvinyl alcohol by weight to the sieved mixed powder and grind for 6 minutes to granulate. Then, put the obtained granules into a cylindrical briquetting mold and press them with a tablet press. First, press the tablets at a pressure of 30MPa for 15 minutes to obtain a preform. Then, press the tablets at a pressure of 300MPa for 7 minutes to obtain the preform.
[0059] S5: The preform is placed in an alumina crucible and fired in a sintering furnace. The furnace is heated from room temperature to 1000℃ at a rate of 10℃ / min, then to 1550℃ at a rate of 5℃ / min. After holding at this temperature for 20 hours, the temperature is further increased to 1800℃ at a rate of 5℃ / min. The heating is then stopped, and the preform is cooled to room temperature to obtain (ZrO2). 0.92 (Y2O3) 0.08 .
[0060] Comparative Example 2
[0061] A ceramic material with the chemical formula (Hf) 0.25 Zr 0.25 Ce 0.25 Y 0.25 O2, the preparation method of which includes the following steps:
[0062] S1: ZrO2 powder, HfO2 powder, CeO2 powder, and Y2O3 powder with a particle size of 40~100nm were placed in a zirconia crucible and calcined at 900℃ for 2.5h to remove moisture and organic impurities from each oxide powder, so that the purity of each oxide powder is ≥99.9%. Then, according to the molar ratio of Hf, Zr, Ce, and Y of 0.25:0.25:0.25:0.25, the calcined ZrO2 powder, HfO2 powder, CeO2 powder, and Y2O3 powder were placed in a zirconia ball mill jar, and anhydrous ethanol and zirconia balls were added for ball milling. The mass ratio of zirconia balls, oxide powder, and anhydrous ethanol was 2:1:0.6. The ball milling speed was 350rpm, and after ball milling for 24h, a uniformly mixed slurry A was obtained.
[0063] S2: Place slurry A in a drying oven and dry it at 80°C for 18 hours to obtain a dry mixed powder. Then grind the dry mixed powder with a mortar and pestle for 6 minutes. Then sieve the ground mixed powder through a 400-mesh sieve. Then introduce the sieved mixed powder into a cylindrical briquetting mold and press it with a tablet press at a pressure of 15 MPa for 10 minutes to obtain a preform.
[0064] S3: Place the preform into an alumina crucible and fire it in a sintering furnace at a temperature of 1300℃ for 30 minutes. Then, crush the fired preform into powder and add anhydrous ethanol and zirconium oxide microspheres to the powder. The mass ratio of zirconium oxide microspheres, oxide powder and anhydrous ethanol is 2:1:0.6. The ball milling speed is 450 rpm and the ball milling is carried out for 36 hours to obtain a uniformly mixed slurry B.
[0065] S4: Place slurry B in a drying oven and dry it at 90℃ for 30 hours to obtain a dry mixed powder. Then grind it with a mortar and pestle for 6 minutes. After grinding, sieve the ground mixed powder through a 500-mesh sieve. Add 8% polyvinyl alcohol by weight to the sieved mixed powder and grind for 6 minutes to granulate. Then, put the obtained granules into a cylindrical briquetting mold and press them with a tablet press. First, press the tablets at a pressure of 30MPa for 15 minutes to obtain a preform. Then, press the tablets at a pressure of 300MPa for 7 minutes to obtain the preform.
[0066] S5: The preform is placed in an alumina crucible and fired in a sintering furnace. The furnace is heated from room temperature to 1000℃ at a rate of 10℃ / min, then to 1550℃ at a rate of 5℃ / min, and held at that temperature for 20 hours. Finally, the temperature is increased to 1800℃ at a rate of 5℃ / min, then the heating is stopped, and the preform is cooled to room temperature to obtain (Hf). 0.25 Zr 0.25 Ce 0.25 Y 0.25 )O2.
[0067] Comparative Example 3
[0068] A ceramic material with the chemical formula (Hf) 0.2 Zr 0.2 Ce 0.2 Y 0.2 La 0.2 O2, the preparation method of which includes the following steps:
[0069] S1: ZrO2 powder, HfO2 powder, CeO2 powder, Y2O3 powder, and La2O3 powder with a particle size of 40~100nm were placed in a zirconia crucible and calcined at 900℃ for 2.5h to remove moisture and organic impurities from each oxide powder, so that the purity of each oxide powder is ≥99.9%. Then, according to the molar ratio of Hf, Zr, Ce, Y, and La of 0.2:0.2:0.2:0.2:0.2, the calcined ZrO2 powder, HfO2 powder, CeO2 powder, Y2O3 powder, and La2O3 powder were placed in a zirconia ball mill jar, and anhydrous ethanol and zirconia balls were added for ball milling. The mass ratio of zirconia balls, oxide powder, and anhydrous ethanol was 2:1:0.6. The ball milling speed was 350rpm, and after ball milling for 24h, a uniformly mixed slurry A was obtained.
[0070] S2: Place slurry A in a drying oven and dry it at 80°C for 18 hours to obtain a dry mixed powder. Then grind the dry mixed powder with a mortar and pestle for 6 minutes. Then sieve the ground mixed powder through a 400-mesh sieve. Then introduce the sieved mixed powder into a cylindrical briquetting mold and press it with a tablet press at a pressure of 15 MPa for 10 minutes to obtain a preform.
[0071] S3: Place the preform into an alumina crucible and fire it in a sintering furnace at a temperature of 1300℃ for 30 minutes. Then, crush the fired preform into powder and add anhydrous ethanol and zirconium oxide microspheres to the powder. The mass ratio of zirconium oxide microspheres, oxide powder and anhydrous ethanol is 2:1:0.6. The ball milling speed is 450 rpm and the ball milling is carried out for 36 hours to obtain a uniformly mixed slurry B.
[0072] S4: Place slurry B in a drying oven and dry it at 90℃ for 30 hours to obtain a dry mixed powder. Then grind it with a mortar and pestle for 6 minutes. After grinding, sieve the ground mixed powder through a 500-mesh sieve. Add 8% polyvinyl alcohol by weight to the sieved mixed powder and grind for 6 minutes to granulate. Then, put the obtained granules into a cylindrical briquetting mold and press them with a tablet press. First, press the tablets at a pressure of 30MPa for 15 minutes to obtain a preform. Then, press the tablets at a pressure of 300MPa for 7 minutes to obtain the preform.
[0073] S5: The preform is placed in an alumina crucible and fired in a sintering furnace. The furnace is heated from room temperature to 1000℃ at a rate of 10℃ / min, then to 1550℃ at a rate of 5℃ / min, and held at that temperature for 20 hours. Finally, the temperature is increased to 1800℃ at a rate of 5℃ / min, then the heating is stopped, and the preform is cooled to room temperature to obtain (Hf).0.2 Zr 0.2 Ce 0.2 Y 0.2 La 0.2 )O2.
[0074] Experimental Example
[0075] I. Structural Testing
[0076] X-ray diffraction tests were performed on the samples prepared in Examples 1-3 and Comparative Example 1, and the results are as follows: Figure 1 As shown, by Figure 1 It can be seen that the XRD results of the sample in the embodiment coincide with the diffraction peaks of the standard card (PDF#38-1439), indicating that the sample prepared by solid-state synthesis in this application has a single-phase cubic fluorite structure.
[0077] The microstructure of the samples prepared in Examples 1-3 and Comparative Example 1 was observed using a scanning electron microscope. The scanning electron microscope images are shown below. Figures 2-5 As shown in the figure, the structure of the sample prepared in the example is relatively dense, and the surface of ceramic blocks with different compositions still has different degrees of porosity.
[0078] The elemental distribution of the samples prepared in Examples 1-3 and Comparative Example 1 was analyzed using an energy dispersive spectroscopy (EDS) instrument. The elemental distribution diagrams of each sample are shown below. Figure 6 As shown.
[0079] II. Anti-CMAS Performance Test
[0080] ① Preparation of CMAS powder
[0081] Weigh the oxide powders according to the molar ratio of CaO, MgO, Al2O3 and SiO2 of 33:9:13:45 and place them in a mortar. Grind the oxide powders thoroughly until the oxides are mixed evenly. Then place the oxide mixture powder in an alumina crucible and sinter it in a high-temperature furnace at 1400℃ for 2 hours. After cooling in the furnace, grind the sintered powder again and pass it through a 500-mesh sieve. The powder after sieving is CMAS powder.
[0082] ② The surfaces of the samples prepared in Examples 1-3 and Comparative Examples 1-3 were ground and polished, then the sample surfaces were cleaned with alcohol, and then the prepared CMAS powder was applied at 15 mg / cm³. 3The coating was uniformly applied to the surface of each sample, which was then placed in an alumina crucible and sintered in a furnace for high-temperature corrosion at 1300℃ for 1h, 4h, and 12h. After corrosion, the corrosion areas of the samples were characterized by XRD, SEM, and EDS. The corrosion depths of each sample were then compared to determine the quality of corrosion. The cross-sectional SEM images of each sample after CMAS corrosion for 1h, 4h, and 12h are shown below. Figures 7-9 As shown in the figure, (a), (b), (c), and (d) are the samples prepared in Comparative Example 1, Example 1, Example 2, and Example 3, respectively. As can be seen from the figure, the corrosion reaction layer formed between the ceramic layer and the CMAS layer in the Example samples, as determined by EDS energy dispersive spectroscopy, consists of two phases: elongated apatite (Ca2RE8(SiO4)6O2) and a rare earth element-stabilized blocky cubic phase (c-ZrO2). In the Example samples, CMAS elements are only present in the corrosion reaction layer and the CMAS residue layer, preventing further penetration of CMAS into the ceramic layer. The corrosion layer or corrosion reaction layer depth of the Example and Comparative Example samples is statistically analyzed in Table 1. The table shows that the corrosion depth and corrosion rate of the Example samples are lower than those of the Comparative Example samples, indicating that the Example samples exhibit excellent resistance to CMAS corrosion, and CMAS did not penetrate the ceramic layer during the entire corrosion process.
[0083] Table 1
[0084]
[0085] III. Thermal conductivity test
[0086] The thermal diffusivity of the ceramic bulk was measured using the laser flash method. A laser thermal conductivity meter (LFA-427, Germany) was used. Before testing, the test temperature was set. A laser pulse was emitted from the laser source and uniformly irradiated the lower surface of the sample. After the surface absorbs the light energy, its temperature rises instantaneously, and it acts as a hot end, transferring the energy to the upper surface via thermal conduction. During this process, an infrared detector continuously measured the temperature rise at the center of the upper surface, ultimately obtaining the temperature-time curve of the sample. The thermal diffusivity was then calculated using formula (1-1). α , in the formula, d and t 1 / 2 These represent the sample thickness and half the time it takes for the upper surface to reach its maximum temperature after absorbing heat, respectively. Then, the sample's thermal conductivity λ is calculated using formula (1-2). ρ and C These represent the density and specific heat capacity of the test sample, respectively.
[0087] (1-1)
[0088] (1-2)
[0089] Thermal conductivity is measured in W·m -1 ·k -1 The results are shown in Table 2. It can be seen from the table that the thermal conductivity of the example sample is significantly lower than that of the comparative sample.
[0090] Table 2
[0091]
[0092] IV. Thermal Expansion Performance Test
[0093] The contact differential method was used to measure the coefficients of thermal expansion of the example and comparative samples at different temperatures. During the test, the error in the coefficients of thermal expansion was almost negligible. After the standard sample was placed in the thermal expansion meter, the temperature was increased, and the difference in thermal expansion was measured. Δl and the temperature difference before and after heating Δt The difference in thermal expansion during the test stems from the varying degrees of thermal expansion between the quartz glass rod and the test sample during the heating process. The coefficient of thermal expansion of the sample is then calculated using formula (1-3). α ,in, α s This represents the coefficient of thermal expansion of quartz glass.
[0094] (1-3)
[0095] The test results are shown in Table 3. It can be seen from the table that the coefficient of thermal expansion of the sample of the example is significantly lower than that of the comparative sample. When it is applied to the preparation of thermal barrier coating materials, the prepared materials can better withstand temperature fluctuations and maintain the stability of the material shape.
[0096] Table 3
[0097]
[0098] Although specific embodiments of the present invention have been described in detail with reference to examples, they should not be construed as limiting the scope of protection of this patent. Various modifications and variations that can be made by those skilled in the art without inventive effort within the scope described in the claims are still within the scope of protection of this patent.
Claims
1. A high entropy ceramic material, characterized in that: The chemical formula of the high entropy ceramic material is (Hf (1-x) / 4 Zr (1-x) / 4Ce (1-x) / 4 Pr (1-x) / 4 Y x ) 2-δ , where the value range of X is 0.08~0.4, and the value range of δ is 0.1~0.
4.
2. The method for preparing the high entropy ceramic material according to claim 1, characterized in that: The following steps are involved: S1: The pretreated oxide powders are mixed according to the element composition in the chemical formula, and the mixture is mixed with a dispersant and ball-milled to obtain slurry A. The oxide powders include ZrO2 powder, HfO2 powder, CeO2 powder, Pr6O 11 powder and Y2O3 powder; S2: drying, grinding, sieving and pressing the slurry A to obtain a prefabricated embryo body; S3: firing the prefabricated body, then crushing the fired body into powder, mixing the powder with the dispersant and ball milling to obtain slurry B; S4: drying, grinding, sieving, granulating and pressing the slurry B to obtain an embryo body; S5: sintering the embryo to obtain.
3. The method for preparing a high entropy ceramic material according to claim 2, characterized in that: The pretreatment of the oxide powder in step S1 is as follows: calcining at 800-1000°C for 2-3h; the particle size of the oxide powder is 40-100nm; ZrO2 powder, HfO2 powder, CeO2 powder, Pr6O 11 The purity of powder and Y2O3 powder is ≥99.9%.
4. The method for preparing a high entropy ceramic material according to claim 3, characterized in that: The dispersant is anhydrous ethanol, and the mass ratio of the oxide powder to the anhydrous ethanol in step S1 is 1:0.5-0.6; the ball milling speed in step S1 is 300-400 rpm, and the ball milling time is 12-48 hours.
5. The method for preparing a high entropy ceramic material according to claim 4, characterized in that: In step S2, the drying temperature is 70-90° C., the drying time is 12-24 h, the grinding time is 5-7 min, the sieving mesh number is 300-500 mesh, and the tablet press is used for pressing, the pressure is 10-20 MPa, and the pressing time is 8-10 min.
6. The method for preparing a high entropy ceramic material according to claim 5, characterized in that: In step S3, the firing temperature is 1200-1400° C., the firing time is 25-50 min, the mass ratio of powder to anhydrous ethanol is 1:0.5-0.6, the ball milling speed is 400-500 rpm, and the ball milling time is 20-50 h.
7. The method for preparing a high entropy ceramic material according to claim 6, characterized in that: In step S4, the drying temperature is 80-100° C., the drying time is 20-40 hours, the grinding time is 5-7 minutes, the sieving mesh number is 500-600 mesh, and the granulation operation is: add 8% of the total weight of polyvinyl alcohol to the sieved mixed powder and grind for 5-7 minutes.
8. The method for preparing a high entropy ceramic material according to claim 7, characterized in that: The pressing operation in step S4 is: using a tablet press to maintain pressure and press for 10 to 20 minutes at a pressure of 20 to 40 MPa, and then to maintain pressure and press for 5 to 8 minutes at a pressure of 250 to 300 MPa.
9. The method for preparing a high entropy ceramic material according to claim 8, characterized in that: The firing method in step S5 is: heating to 1000°C at a heating rate of 10°C / min, then heating to 1550°C at a heating rate of 5°C / min, keeping the temperature for 20 hours, then heating to 1800°C at a heating rate of 5°C / min, then stopping heating and cooling to room temperature.
10. An application of a high entropy ceramic material, characterized in that: The high entropy ceramic material according to claim 1 is used to prepare a thermal barrier coating material.
Citation Information
Patent Citations
Complex oxide thermal barrier coatings with low thermal inertia and low thermal conductivity
CA3197162A1
High-entropy composite oxide and preparation method and application thereof
CN118458819A